IMPLEMENTASI KEBIJAKAN PENANGANAN GELANDANGAN, PENGEMIS, TUNA SUSILA DAN ANAK JALANAN DI KOTA PALANGKA RAYA - Imanuel Jaya (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2019)
The problems of social welfare that are developing today show that there are citizens who have not fulfilled their basic needs properly because they have not received social services from the state. The existence of homeless people, beggars, prostitutes and street children is a joint task that must be immediately addressed by the Central Government and the Regional Government. In particular, the City Government of Palangka Raya has issued a policy contained in Regional Regulation No. 09 of 2012 concerning Handling of Bums, Beggars, Prostitutes and Street Children. Where this policy aims to provide understanding and skills for actors to be able to live normally in society. The theory used is George Edward III about policy implementation which consists of four indicators, namely, Communication, Resources, Disposition and Structure of the Bureaucracy. This study uses a descriptive research method with a qualitative approach that is obtained based on the researchers' reasoning ability in connecting facts, data, and information obtained during the research. The study was conducted in the City of Palangka Raya, the Office of Social Services of the City of Palangka Raya. Data collection methods used in the form of observation, interviews, and documents. Analysis of the data used is data reduction, data presentation and conclusion drawing. Based on the results of the study, related to the Implementation of the Homeless Handling Policy of Beggars and Street Children in Palangka Raya City, the results have been implemented for 6 years but have not had a significant impact. Lack of communication between related parties, inadequate human resources, Disposition (attitude) Implementing policies that have not been decisive become the main factor in the lack of maximum handling. As a supporting and inhibiting factor (Internal), so far the Social Service has received a budget from the Government in carrying out short-term handling in the form of enforcement, rehabilitation (social and mental) and repatriation to the place of origin. As a limiting factor, in the long run the local government still does not have a social rehabilitation institution to provide work skills and social guidance. While from (External) which is a supporting and inhibiting factor is the culture of the community to be together care and not neglect, Political Wiill, and Regulation for the benefit of the community.